Fuzzy Controller to Prepare the Dialysate Solution in Hemodialysis Machine: المتحكم الضبابي لتحضير محلول الديلزة في جهاز غسيل الكلية - Shaza Yasser Shehada, Joumana Mahmoud Diab, Ahmad Suliman Ahmad (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2019)
We concentrate on designing a fuzzy controller, its task is management the operation of preparing the dialysate solution with the required Specifications and continuous monitoring to set the value of conductivity that takes major role to success the bloody Purification operation, where any error in this operation lead to reduce the efficiency of hemodialysis machine so the patient will face the damage. In this research, we reduced the time to treatment (TTT) by speeding the preparing operation of the dialysate solution, and achieve more reliable value of required conductivity so it reduces the alarms that result of override the allowable values which lead to stop the preparing operation and wait for the required values. The fuzzy controller gave us more efficiency when we compared with other controllers which was achieved in previous researches, so we can use the learning algorithms to make this controller more adaptive.